Universalism(e): Conversations - Cohen, Elsie; Deiab, Azyza; Hofmann, Franck; Messling, Markus; Ndé Fongang, Clément; Thiérard, Hélène; Tinius, Jonas (Beyond Universalism / Partager l’universel, 2024)
Those who look for the traces of a new universalism of our time are themselves its critical builders. The conversations documented in this book echo recordings of encounters online, and sow their own traces of a minor universalism that can be imagined in-between and across differences. Conversations with: Arjun Appadurai, Leyla Dakhli, Souleymane Bachir Diagne, Giovanni Levi, Gisèle Sapiro, David Scott, Adania Shibli, and Maria Stavrinaki.